2022
DOI: 10.54527/jdir.2022.41.4.91
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of accuracy of different elastomeric materials in open tray implant level technique for single tooth impressions

Abstract: Purpose: This study compared the accuracy of different elastomeric impression materials with open tray implant level impression technique in a single-tooth replacement. Materials and Methods:A reference model representing a single implant with an adjacent simulated natural tooth was fabricated. Open tray implant level impressions were made with vinylpolysiloxane (light body ExpressXT, PentaputtyPentamix2, 3MESPE, Seinfield, Germany) (Group I, n=10) and polyether (medium body Impregnum Penta, Pentamix 2, 3MESPE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Dental Implantology is a prosthetically driven science, where an accurate impression is the primary foundation for successful reconstruction [ 14 ]. The accuracy of impression is influenced by various factors, such as depth, angulation and position of implants, impression materials, impression technique, type of impression trays, level of impression (implant/abutment level), design of impression coping, splinting or non-splinting of impression coping, and time delay for impression pouring [ 15 ]. The results of the study showed that, in deeply placed subgingival implants, the PE impression material provided statistically significant stability to impression coping compared to the PVS impression material.…”
Section: Discussionmentioning
confidence: 99%
“…Dental Implantology is a prosthetically driven science, where an accurate impression is the primary foundation for successful reconstruction [ 14 ]. The accuracy of impression is influenced by various factors, such as depth, angulation and position of implants, impression materials, impression technique, type of impression trays, level of impression (implant/abutment level), design of impression coping, splinting or non-splinting of impression coping, and time delay for impression pouring [ 15 ]. The results of the study showed that, in deeply placed subgingival implants, the PE impression material provided statistically significant stability to impression coping compared to the PVS impression material.…”
Section: Discussionmentioning
confidence: 99%